Germline variants in the Von Hippel-Lindau tumor suppressor gene in Cuban patients - Antonio Alejandro Esperón Álvarez; Inés Virginia Noa Hechavarría; Ixchel López Reyes; Teresa Collazo Mesa (Egyptian Journal of Medical Human Genetics, 2024)
Abstract Background Von Hippel-Lindau (VHL) syndrome is an autosomal dominantly inherited disorder that predisposes to multiple neoplasms. Patients may develop hemangioblastomas of the central nervous system and retina, multiple cysts in the pancreas and kidneys, renal carcinoma, and pheochromocytomas, among other lesions. This disease is caused by germline genetic variants in the VHL gene. The regulation of the alpha subunit of hypoxia-inducible factor-1 is the key tumor suppressor function of the VHL protein. To date, more than seven hundred variants have been reported in VHL gene. This study aimed to investigate the molecular etiology of VHL syndrome in Cuban patients. Results DNA samples from twenty-two individuals were analyzed by Sanger sequencing or enzymatic restriction. The analysis identified four novel pathogenic variants for the Cuban population: c.463 + 2T > C, C162W, R167W, and S183X, in addition to D121G and R161X, previously described in another work. The diagnosis was confirmed in seven patients with clinical manifestations and family history. Two at-risk family members without clinical signs were positive for presymptomatic diagnosis. Conclusions The spectrum of germinal point mutations of VHL gene in Cuban patients was updated. The presence of genetic variants was ruled out in eight asymptomatic relatives, which is a psychological relief for these individuals. The results allow for offering other at-risk relatives the presymptomatic diagnosis and the possibility of receiving genetic counseling.